Organic Enrichment Induces Shifts in the Trophic Position of Infauna in a Subtropical Benthic Food Web, Hong Kong - Xu, Wenzhe; Shin, Paul K. S.; Sun, Jun (Frontiers in Marine Science, 2022)
Anthropogenic nutrient input to coastal waters is one of the most common disturbances within inshore marine benthic communities. Organic enrichment in sediments leads to the reduction or disappearance of sensitive organisms, and influences the quality and quantity of primary producers which serve as food sources for the benthic fauna. Such changes, in turn, affect the energy flow and food-web interactions in benthic communities. To examine how organic enrichment may alter marine benthic trophic relationship, a stable isotope (δ13C and δ15N) analysis of the potential food sources and a range of meiofauna and polychaetes from an organically polluted and a relatively unpolluted site was compared in subtropical waters of Hong Kong. Results indicated that some omnivorous infauna shifted from a mainly carnivorous diet at the unpolluted site to a largely herbivorous diet at the organically polluted site. This dietary shift is likely to be related to the oxygen stress, prey limitation and increased abundance and nutritional quality of primary producers in the eutrophic area, resulting in an increase in utilization of plant materials as the major food source. The present findings suggest that such changes in trophic position induced by organic enrichment can provide further insights into the structure and function of coastal benthic communities under pollution stress.